Zooplankton Feeding Induces Macroscopical Gonad Malformations in Whitefish (Coregonus ssp.) from Lake Thun, Switzerland - Daniel Bernet; Thomas Wahli; Christoph Küng; Helmut Segner (Fishes, 2020)
Alterations in gonad morphology are widespread in wild fish populations. Whitefish (Coregonus spp.) from Lake Thun, Switzerland, display a high prevalence of macroscopical gonad malformations including fusions to the musculature, segmented gonads and intersex condition. The aim of the present study was to evaluate whether the gonad morphological changes in Lake Thun whitefish are caused by genetic factors, environmental factors (water, diet) or “gene × environment” interaction. We performed two independent experiments of a three-year duration in which we reared whitefish from fertilization until adulthood and tested the possible causative factors using a matrix design: (i) genetics—comparing the prevalence of gonad malformations in whitefish of different genetic origin reared under identical environmental conditions (same diet, same water, same experimental facility); (ii) environment—comparing the prevalence of gonad malformations in whitefish of the same genetic origin reared in different water sources and/or fed with different diets; and (iii) gene-environment interaction—comparing the prevalence of gonad morphological alterations in relation to the combinations of genetics and environmental factors. Two diets were used for the rearing experiments: either zooplankton collected in Lake Thun which represents the natural diet of whitefish, or an artificial dry food which was used as control. The key finding of this study is that the inducing factor of the gonad malformations is contained in the zooplankton of Lake Thun. Fish fed with this diet developed a significantly higher prevalence of malformations than fish from any other treatment, irrespective of the genetic origin and/or the water source. This result could be repeated in the two independent experiments. Importantly, the prevalence values observed in the experimental fish fed with Lake Thun zooplankton were similar to the prevalence values recorded in free-ranging whitefish in the lake. The findings of this study advance the understanding of the causes of gonad morphological alterations in wild fish populations.